Behavioral disorders caused by nonylphenol and strategies for protection. (July 2021) - Lu, Dezhi; Yu, Leilei; Li, Miaoyu; Zhai, Qixiao; Tian, Fengwei; Chen, Wei
Abstract: Nonylphenol (NP) is widely used in daily production and life due to its good emulsification. In this review, we discuss toxicology studies that examined behavioral disorders caused by NP, the corresponding toxicological mechanisms in the central nervous system (CNS), and strategies for protection. Available in vitro and in vivo evidence suggests that exposure to NP during adulthood or early childhood is associated with cognitive dysfunction, including depression-like behaviors, anxiety-like behaviors, and impaired learning and memory. The main mechanisms underlying NP-related cognitive disorders include inflammation, destruction of synaptic plasticity, and destruction of important signaling pathways that affect the synthesis and secretion of neurotransmitters. The effects and mechanisms of NP exposure on CNS-mediated reproductive function, including interference with the expression of hormones, proteins, and enzymes, are discussed. Other abnormal behaviors such as locomotor activity and swimming behavior are also described. Several measures to prevent NP neurotoxicity are summarized. These measures are based on the toxicological mechanisms underlying NP exposure and include external protection and internal self-regulation of the nervous system. Finally, a new treatment idea is proposed based on the gut–brain axis. Characterizing the behavioral changes and underlying toxicity mechanisms associated with NP exposure and investigating the possible methods of treatment will help to expand the understanding of these mechanisms and could lead to more effective treatments. Graphical abstract: Image 1 Highlights: The behavioral abnormalities characteristics caused by NP were presented. The potential mechanism of NP causing abnormal behaviors were summarized. New potential perspectives were provided for the protection of NP neurotoxicity.